Sosialisasi Dalam Meningkatkan Kesadaran Tentang Pentingnya Membayar Pajak dan Retribusi - Yohanis Rante (The Community Engagement Journal, 2023)
Taxes and retribution are important things in supporting economy condition, especially for the state. The existence of socialization regarding taxes and the importance of paying taxes to traders/entrepreneurs is expected to increase their level of awareness, trust and compliance as taxpayers that will increase the awareness of paying taxes. When people have awareness, paying taxes will be done voluntarily, not compulsorily, thus helping local governments in maximizing tax revenues that can be used fully in the development process to improve people's welfare. The purpose of this activity is traders around the Cigombong Market, VIM Village in Jayapura City. Traders can know the importance of awareness in paying taxes and retribution in Jayapura City, and traders can practice how to pay taxes and retribution in Jayapura City. The results of this activity in general, include the achievement of objectives regarding knowledge, understanding the importance of taxes and retribution and practicing how to pay. There were 18 traders who came as participants. They are willing to continue this information to traders around Cigombong who did not have time to attend the socialization. Overall, the activity can run smoothly and success.Keywords: Socialization, Taxes, Retribution